AKTIVITAS ANTIBAKTERI EKSTRAK KULIT BUAH MANGGIS (Garcinia mangostana L.) SERTA KANDUNGAN SENYAWA AKTIFNYA [Antibacterial Activity of Mangosteen (Garcinia mangostana L.) Husk Extract, and its Active Compounds] - I Nengah Kencan Putra (Jurnal Teknologi dan Industri Pangan, 2010)
Mangosteen husk is traditionally has been used by palm sugar farmers for preserving palm sap.  This research was aimed to determine the  antibacterial activity of mangosteen husk extract against Leuconostoc mesenteroides and Lactobacillus plantarum (which  are the most common palm sap-spoiling bacteria), and to analyze the active compounds of the extract. Methanol extract of mangosteen husk showed antibacterial activity against both L. mesenteroides and L. plantarum with inhibition zone diameter of 12.70 and 11.02 mm respectively.  Observation on the fractions of the extract showed that chloroform and ethyl acetate fractions exhibited antibacterial activity  on the above bacteria . Identification of the active compounds performed by GC-MS showed that the dominant compound  in the chloroform extract was 9, 10-anthracenedione, while that in  the ethyl acetate extract was  7H-furo 3’,2’:4,5 furo 2,3-c xanthen-7-one.  Those compounds belonged to the derivate of anthraquinone and xanthone respectively.